How reasonable is the reasonable royalty rate?: Damage rules and probabilistic intellectual property rights - Jay Pil Choi (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper investigates how different damage rules in patent infringement cases shape competition when intellectual property rights are probabilistic. I develop a simple model of oligopolistic competition to compare two main liability doctrines that have been used in the US to assess infringement damages - the unjust enrichment rule and the lost profit rule. It also points out the logical inconsistency in the concept of the reasonable royalty rates when intellectual property rights are not ironclad.
Keywords: O3; L1; L4; D8; K4; 330